Senif Penerima Zakat: Sebuah Upaya Untuk Reinterpretasi - Al Yasa` Abubakar (Media Syari'ah, 2017)
This article would like to see and discuss the opinion of the scholars of the eight groups of zakat recipients, especially in relation to the distribution of zakat purposes at the present time. How the eight groups in the present time must be defined, after a change and such a large social differences between the school friend and priest in the seventh century to ten Miladiah first, to the Muslims now, at the beginning of the 21st century. At first the Muslims may be said to live in the age of agraris (farming), while now they’ve moved into the industrial age, who say the new emerging world (society) Muslims since the beginning of the twentieth century.